2010
DOI: 10.3928/01477447-20100225-26
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Granulomatous Tenosynovitis Treated With Ulnar Superficialis Slip Resection

Abstract: Ulnar superficialis slip resection is a procedure initially performed to treat flexor tenosynovitis in the rheumatoid finger. It was first described for treating trigger digits of children with mucopolysaccharide storage disorders and for more complex trigger digits in children. The procedure for adults with trigger finger was described for triggering with flexion contracture at the proximal interphalangeal joint level persisting after release of the A1 pulley and for trigger finger in diabetic patients.This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Our findings suggest that since the higher load to failure slip in the second and third digits is the ulnar FDS slip it should not be sacrificed 4,7,8 but rather the radial slip of the FDS should be sacrificed in these digits. Marcus et al 7 as well as Rubin et al 8 chose to sacrifice the ulnar slips of the FDS in 2 different clinical settings; trigger finger release in diabetics and chronic granulomatous tenosynovitis respectively, based on the assumption that the ulnar FDS slip is the less dominant one in all digits. Our findings challenge this belief: in the second and third digits the breaking point of the ulnar slips of the FDS was greater and hence we perceive the ulnar slip as the dominant one and the radial FDS slip should be sacrificed in these digits.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our findings suggest that since the higher load to failure slip in the second and third digits is the ulnar FDS slip it should not be sacrificed 4,7,8 but rather the radial slip of the FDS should be sacrificed in these digits. Marcus et al 7 as well as Rubin et al 8 chose to sacrifice the ulnar slips of the FDS in 2 different clinical settings; trigger finger release in diabetics and chronic granulomatous tenosynovitis respectively, based on the assumption that the ulnar FDS slip is the less dominant one in all digits. Our findings challenge this belief: in the second and third digits the breaking point of the ulnar slips of the FDS was greater and hence we perceive the ulnar slip as the dominant one and the radial FDS slip should be sacrificed in these digits.…”
Section: Discussionmentioning
confidence: 73%
“…Sacrifice of one of the slips of the FDS has been suggested as a possible solution for “overstuffing” or “crammed” flexor tendon repairs. 3-12 Sacrifice of one of the FDS slips can be considered as the treatment of choice when enlarged tendons are encountered following chronic synovitis (and thus finger triggering and stiffness) and trigger finger conditions including pediatric trigger finger. 13,14…”
Section: Introductorymentioning
confidence: 99%
“…In such cases, reduction in total flexor tendon volume by half superficialis slip resection or reduction flexor tenoplasty of the FDP was needed with or without A3 or partial A2 pulley release in most situations. 1,[9][10][11] There have been reports of histopathologic studies of hypertrophic A1 pulleys of trigger fingers, but reports about the affected flexor tendon itself and the tenosynovium covering the tendons have been very few. [12][13][14] Lundin et al 12 reported that tendinosis, which was characterized by micro-ruptures, collagen degradation, or hyper-and hypocellularity, occurred in trigger finger, and these findings suggest that trigger finger could start within the tendon, not only the pulley or tenosynovium.…”
Section: Discussionmentioning
confidence: 99%
“…First, the thickened ulnar half-slip of the FDS was detached and resected at the chiasma level according to ulnar superficialis slip resection (USSR) to reduce the total flexor tendon volume. 1,10 However, after this procedure, the tendon entrapment was not completely released and FDP gliding when passing through the A2 pulley was not smooth. Then, the FDP was made slender as in partial longitudinal spindle-shaped removal within an enlarged tendon (►Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…When all synovitis is resected, a longitudinal partial resection of the tendon may be considered; however, this is rarely needed if the A1 pulley is properly incised. 8,9 In patients with rheumatoid arthritis, the A1 pulley should not be released for fear of tendon bowstringing and digital ulnar drift. Instead, the tenosynovitis should be excised.…”
mentioning
confidence: 99%